ANALISIS KONTRIBUSI MEDIA PEMBELAJARAN BERBANTUAN CANVA TERHADAP DORONGAN (MOTIVASI) BELAJAR SISWA PADA UNIT PEMBELAJARAN SISTEM DAN ALAT PEMBAYARAN DI SMA - Aulia, Nazwa; Revita Yuni; Cintya Putri Nasution; Dia Aulia Harahap; Tiara Marsya Aulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student learning motivation in economics subjects, particularly on payment systems and means of payment, remains a problem in senior high school learning. Therefore, digital learning media that can present material visually and interactively are needed. This study aims to analyze the effect of Canva-based learning media on students’ learning motivation and to provide empirical evidence regarding the integration of creative digital platforms in economics learning. This research employed a quantitative approach with an exploratory research design. The research sample consisted of 61 students who participated in learning activities using Canva-based media. Data were collected through a Likert-scale questionnaire that had been tested for validity using Product Moment correlation and for reliability using Cronbach’s Alpha coefficient. Data analysis was conducted through classical assumption tests and simple linear regression analysis. The results show that Canva-based learning media have a positive and significant effect on students’ learning motivation. The correlation value R = 0.802 indicates a very strong relationship, while the coefficient of determination R² = 0.643 shows that 64.3% of the variance in learning motivation is explained by the use of Canva media. The regression coefficient β = 0.752; sig. 0.000 confirms increased student motivation, while 35.7% is influenced by factors outside Canva media.